2012
DOI: 10.1016/j.aeolia.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of RWEQ in a patchy landscape; a first step towards a regional scale wind erosion model

Abstract: a b s t r a c tDespite the fact that wind erosion seriously affects the sustainable use of land in a large part of the world, validated wind erosion model that predicts windblown mass transport on a regional scale is lacking. The objectives of this research were to modify revised wind erosion equation (RWEQ) to estimate soil loss at a field scale in a way that it could operate at a regional scale, to calibrate the model using ground data collected from a field scale representing different land uses in Khanasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 22 publications
(22 reference statements)
0
28
0
1
Order By: Relevance
“…In this study, the RWEQ model was selected because it has proven to be an effective tool (Buschiazzo & Zobeck, ; Youssef et al, ), with a straightforward modelling scheme and only a limited amount of input data. The first attempt to up‐scale RWEQ was carried out in Texas by Zobeck et al (), where the RWEQ software was employed to predict the soil loss for a number of representative fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the RWEQ model was selected because it has proven to be an effective tool (Buschiazzo & Zobeck, ; Youssef et al, ), with a straightforward modelling scheme and only a limited amount of input data. The first attempt to up‐scale RWEQ was carried out in Texas by Zobeck et al (), where the RWEQ software was employed to predict the soil loss for a number of representative fields.…”
Section: Discussionmentioning
confidence: 99%
“…The equation is relatively simple and requires a limited amount of input data, which makes it suitable for upscaling (Zobeck et al, ; Youssef et al, ; Guo et al, ). Wind is the basic driving force in the model.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, erosion that occurs in one land unit affects the units located downwind. Todd et al (2004), Fryrear et al (1998) and Youssef et al (2012) studied the effect on the maximum sediment transport and reported a gradual increase in the mass flux from bare land downwind from a non-erodible border. Therefore, to understand the effect of vegetation at the regional scale, it is vital to generate data representing processes taking place along the entire land unit and at transitions between land units.…”
Section: Introductionmentioning
confidence: 96%
“…In the study of Shao and Leslie (1997) measured wind transport data from a one-week survey, were scaled up to the continental scale of Australia by GIS methods, resulting in estimates that were generally problematic, because of the spatial validity of the data. By testing the calibration of RWEQ on Syrian study sites up to 150 ha in size, it was possible to acquire regional-scale results of good quality (Buschiazzo et al, 1999;Fryrear et al, 1998;Youssef et al;. Nevertheless, the plot-sized models have intense data requirements that are difficult to meet even on the local scale.…”
Section: Wind Erosion Modelling In Local and Regional Scalementioning
confidence: 99%